Identification of degrader bacteria and fungi enriched in rhizosphere soil from a toluene phytoremediation site using DNA stable isotope probing. Issue 8 (3rd July 2021) - BenIsrael, Michael; Habtewold, Jemaneh Z.; Khosla, Kamini; Wanner, Philipp; Aravena, Ramon; Parker, Beth L.; Haack, Elizabeth A.; Tsao, David T.; Dunfield, Kari E.
Abstract: Improved knowledge of the ecology of contaminant-degrading organisms is paramount for effective assessment and remediation of aromatic hydrocarbon-impacted sites. DNA stable isotope probing was used herein to identify autochthonous degraders in rhizosphere soil from a hybrid poplar phytoremediation system incubated under semi-field-simulated conditions. High-throughput sequencing of bacterial 16S rRNA and fungal internal transcribed spacer (ITS) rRNA genes in metagenomic samples separated according to nucleic acid buoyant density was used to identify putative toluene degraders. Degrader bacteria were found mainly within the Actinobacteria and Proteobacteria phyla and classified predominantly as Cupriavidus, Rhodococcus, Luteimonas, Burkholderiaceae, Azoarcus, Cellulomonadaceae, and Pseudomonas organisms. Purpureocillium lilacinum and Mortierella alpina fungi were also found to assimilate toluene, while several strains of the fungal poplar endophyte Mortierella elongatus were indirectly implicated as potential degraders. Finally, PICRUSt2 predictive taxonomic functional modeling of 16S rRNA genes was performed to validate successful isolation of stable isotope-labeled DNA in density-resolved samples. Four unique sequences, classified within the Bdellovibrionaceae, Intrasporangiaceae, or Chitinophagaceae families, or within the Sphingobacteriales order were absent from PICRUSt2-generated models and represent potentially novel putative toluene-degrading species. This study illustrates the power of combining stable isotope amendment with advanced metagenomic and bioinformatic techniques to link biodegradation activity with unisolated microorganisms. Novelty statement: This study used emerging molecular biological techniques to identify known and new organisms implicated in aromatic hydrocarbon biodegradation from a field-scale phytoremediation system, including organisms with phyto-specific relevance and having potential for downstream applications (amendment or monitoring) in future and existing systems. Additional novelty in this study comes from the use of taxonomic functional modeling approaches for validation of stable isotope probing techniques. This study provides a basis for expanding existing reference databases of known aromatic hydrocarbon degraders from field-applicable sources and offers technological improvements for future site assessment and management purposes.